The gray zone: sovereignty, human smuggling, and undercover police investigation in Europe - Feldman, Gregory (Anthropology of policy, 2019)
Cover -- Contents -- Preface -- The Argument -- Acknowledgments -- Introduction: Sovereignties and Their Gray Zones -- 1. The Ambiguity of Truth: The Ephemeral Limits of Security Apparatuses -- 2. Identity and the Investigative Team: Violence, Sovereignty, and Personhood -- 3. The Thinness of Secrecy -- 4. Sovereign Actions on a Global Stage -- Conclusion: Alternatives Within: The Appearance of the Second Sovereign Form Despite the First -- References -- Index